Suspension High Velocity Oxy-Fuel (SHVOF)-sprayed alumina coatings: microstructure, nanoindentation and wear - Murray, J.W.; Ang, A.S.M.; Pala, Z.; Shaw, E.C.; Hussain, T. (Springer, 2016)
Suspension High Velocity Oxy Fuel Spraying (SHVOF) can be used to produce thermally sprayed coatings from powdered feedstocks too small to be processed by mechanical feeders, allowing formation of nanostructured coatings with improved density and mechanical properties. Here, alumina coatings were produced from sub-micron sized feedstock in aqueous suspension, using two flame combustion parameters yielding contrasting microstructures. Both coatings were tested in dry sliding wear conditions with an alumina counterbody. The coating processed with high combustion power of 101 kW contained 74 wt% amorphous phase and 26 wt% crystalline phase (95 wt% gamma and 3 wt% alpha alumina) while the 72 kW coating contained lower 58 wt% amorphous phase and 42 wt% crystalline phases (73 wt% was alpha and 26 wt % gamma). The 101 kW coating had a dry sliding specific wear rate between 4-4.5 x 10-5 mm3/Nm, 2 orders of magnitude higher than the 72 kW coating wear rate of 2-4.2 x 10-7 mm3/Nm. A severe wear regime dominated by brittle fracture and grain pull out of the coating was responsible for the wear of the 101 kW coating, explained by mean fracture toughness three times lower than the 72 kW coating, owing to the almost complete absence of alpha alumina.